The Influence of the Team Games Tournament Type Cooperative Learning Model on Anecdotal Text Writing Skills: - Maharani, Vivi; Puspitoningrum, Encil; Pitoyo, Andri (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe: 1) the results of the pre-test of anecdotal text writing skills of class X students of SMA Negeri 4 Kediri per sample group; 2) the results of the post-test of anecdotal text writing skills of class X students of SMA Negeri 4 Kediri per sample group; 3) the presence or absence of the influence of the use of team games tournament (TGT) in learning anecdotal text writing skills in the treatment group of class X students of SMA Negeri 4 Kediri. This research was conducted at SMA Negeri 4 Kediri in the 2024/2025 academic year. The population of this study consisted of 35 students from Class X-5 and 34 students from Class X-6 who participated in the pre-test, teaching, and learning activities focused on anecdotal text writing skills, as well as the post-test. The sample consisted of 34 students from class X-5 and 33 students from class X-6. The researcher, who employed a quantitative descriptive method in this quasi-experiment, utilized a pretest-posttest control group design. Data on anecdotal text writing skills were collected using a performance test instrument that was arranged objectively and systematically. Data analysis using parametric inferential statistics analysis, namely a one-sample t-test for the first and second objectives and an independent sample t-test for the third objective. The results of the study: 1) the pre-test results of the anecdote text writing skills of class X students of SMA Negeri 4 Kediri per sample group are in the low category; 2) the post-test results of the anecdote text writing skills of class X students of SMA Negeri 4 Kediri in the treatment group are higher than the control group; 3) there is a positive influence of the use of TGT in learning the anecdote text writing skills in the treatment group of class X students of SMA Negeri 4 Kediri.